AL-QUR'AN SEBAGAI SUMBER ETIKA DALAM BISNIS DAN EKONOMI KONTEMPORER: (The Qur'an as a Source of Ethics in Contemporary Business and Economics) - Yasser Muda Lubis (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
Ethics in contemporary business and economics is an important concern in the current era of globalization. The Qur'an, as the holy book of Muslims, offers comprehensive moral and ethical guidelines. This research aims to examine how the Al-Qur'an can be used as a source of ethics in business practices. This research uses a qualitative approach with a literature review method. Primary data sources come from relevant verses of the Qur'an, while secondary data is obtained from literature related to business ethics, Islamic economics, and interpretations of classical and contemporary ulama. Analysis shows that the Qur'an contains ethical principles that can be applied in business and economics, such as justice, honesty, responsibility, transparency and integrity. These principles serve as a strong moral foundation to guide behavior and decisions in the modern business context. The implementation of Al-Qur'an ethics in contemporary business faces challenges and opportunities. Challenges include cultural differences, application of these principles amidst the complexity of the global economy and also differences in interpretation. However, opportunities include increasing trust and integrity in business, as well as contributing to equitable economic development. The integration of Qur'anic values ​​in business practices can produce significant positive impacts, both morally and economically.